A Thymoma (Case Report): Importance of Comorbidity, Lifestyle, and Thymoma Size in Treatment Success - Suryaman, Rachmat; Djajalaksana, Susanthy; Setyawan, Ungky; Wardhana, Koernia; Erawati, Dini; Yudhanto, Hendy (Universitaas Brawijaya, 2022)
Thymoma is a rare malignancy with an incidence of 0,15 case per 100.000 population and is the most commonly diagnosed anterior mediastinal malignancy. With 12,5% 15-year survival rate, and is often accompanied by autoimmune disease such as myasthenia gravis, pure red blood cell aplasia, and hypogammaglobulinemia, better understanding of factors affecting prognosis is needed to improve patient quality of life and survival.